LAW RELATING TO STALKING IN INDIA (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Due to the digital age's changing understanding of personal boundaries and permission, India's anti-stalking law has reduced harassment and violence against women. After the 2012 Delhi gang rape case, the Criminal legislation (Amendment) Act of 2013 added Section 354D to the Indian Penal Code, the stalking legislation. Laws against online and offline stalking emphasise respecting a person's rejection and stalker persistence. Section 354D penalises first-time offenders for three years and future offenders for five years. Since gender conventions and wooing might conflate stalking and persistent love pursuit, these principles may work depending on the social setting. While stalking laws have heightened awareness and problems about internet ethics, personal limitations, and authorisation, The 2013 Criminal Law (Amendment) Act criminalised stalking, a critical gender-based violence prevention strategy, and reminded stalkers that it was wrong. Digital technology has changed human communication, including cyberstalking, a dangerous type of stalking. The Information Technology Act, 2000 governs cyberstalking in India, however inadequate regulations and police have caused problems. Law enforcement struggles to detect and convict stalkers because to a lack of education and training in stalking and attitude issues and the intricacy of cyberstalking. The perception that stalking in ex-relationships is less severe and the lack of resources to examine online victim complaints complicate matters. Stalking laws in many nations depend on police enforcement, which must recognise stalking's violent nature, set reporting regulations, and educate personnel differently. The 1996 Interstate Stalking Punishment and Prevention Act criminalisescyberstalking and interstate stalking in the US and UK. UK stalking laws include restraining orders and SPOs, which protect victims without criminal conviction. The 2013 Criminal Law (Amendment) Act in India criminalised stalking, strengthening sexual harassment and assault prohibitions. The Indian law prioritises punishment after the offence, therefore victims receive little immediate protection. The Indian Penal Code covers sexual harassment, assault, voyeurism, and cyberstalking. The US and UK prioritise victim protection and allow law enforcement to act before stalking increases, but India's penalty does not work.